1998
DOI: 10.1002/(sici)1097-4660(199809)73:1<54::aid-jctb916>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Saccharomyces cerevisiae immobilized onto chrysotile for ethanol production

Abstract: : Saccharomyces cerevisiae (CCT 3174 and commercial bakerÏs yeast) was immobilized by adsorption onto chrysotile. The adsorbed yeast cells were easily washed out, but cells grown in situ were strongly attached by entrapment by chrysotile microÐbres. In fermentation experiments with 30% (w/v) glucose solution, the immobilized cells showed a 1É3-fold increase in initial reaction velocity. For immobilized CCT 3174, the Ðnal ethanol yield was 26% higher than that with free cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Moreover higher evolution of CO 2 in the flasks with wrapped chrysotile showed that the form in which chrysotile was present in the fermentation medium influenced the yeast activity. The changes in the productivity obtained for systems with immobilized cells on chrysotile could be explained by strong interaction between chrysotile and cells, which affected the structure of cells membrane (Joekes et al, 1998). To confirm if the catalytic effect of chrysotile on the acceleration of alcoholic fermentation did not occur only the first time that it was used, the chrysotile used in the experiments of the Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover higher evolution of CO 2 in the flasks with wrapped chrysotile showed that the form in which chrysotile was present in the fermentation medium influenced the yeast activity. The changes in the productivity obtained for systems with immobilized cells on chrysotile could be explained by strong interaction between chrysotile and cells, which affected the structure of cells membrane (Joekes et al, 1998). To confirm if the catalytic effect of chrysotile on the acceleration of alcoholic fermentation did not occur only the first time that it was used, the chrysotile used in the experiments of the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chrysotile is a mineral of magnesium silicate present in nature in a fibrous form. It has an exceptional capability to immobilize yeast cells by adsorption, with some advantages when compared to the carriers cited in the literature, as it has excellent stability that allows its use for long periods and for reuse, shows resistance to thermal treatment, supports operational conditions of alcoholic fermentation, and is cheep (Moran et al, 1997), but the main advantage of this mineral is its stimulation of the ethanol production by yeast, increasing the specific productivity of the processes (Wendhausen et al, 2001;Filloy et al, 2001;Joekes et al, 1998). The aim of this work was to investigate ethanol production by Saccharomyces cerevisiae cells supported on chrysotile, under non-aseptic conditions in continuous and batch fermentations, using diluted sugar-cane molasses as the source of carbon.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysotile is a hydrated magnesium silicate of the serpentine group of minerals whose chemical composition may be given stoichiometrically as Mg 3 Si 2 O 5 (OH) 4 . Its major use is in cement composites, but new applications have explored its action as an efficient catalyst or catalyst support [4][5][6].…”
Section: Co2 + 14 H 2 O + Nahso 3 (1)mentioning
confidence: 99%
“…Entrapment has been one of the most used methods for whole cell entrapment due to its simplicity and non-toxic character (Ghorbani et al 2011). Until now, many types of natural and inorganic support materials such as sodium alginate beads (Najafpour et al 2004), sorghum bagasse (Yu et al 2007), zeolite (Shindo et al 2001), grape skin (Mallouchos et al 2002), glass beads (Arasaratnam and Balasubramaniam 1998), chrysotile (Joekes et al 1998), and agar (Behera et al 2010, Lebeau et al 1997) for yeast immobilization have been used for ethanol production.…”
Section: Introductionmentioning
confidence: 99%